Facile Synthesis of 3D Anode Assembly with Si Nanoparticles Sealed in Highly Pure Few Layer Graphene Deposited on Porous Current Collector for Long Life Li‐Ion Battery. Issue 10 (3rd March 2017) - Shelke, Manjusha V.; Gullapalli, Hemtej; Kalaga, Kaushik; Rodrigues, Marco‐Tulio F.; Devarapalli, Rami Reddy; Vajtai, Robert; Ajayan, Pulickel M.
Abstract : With its exceptional theoretical charge capacity, silicon holds great promise as an anode material for realization of high energy density Li‐ion batteries. However, extensive volume expansion and poor cycle stability of silicon compromise its actual use. In an effort to tame volume expansion and structural disintegration during cycling, an innovative 3D electrode assembly is fabricated involving continuous layer of graphene coated on porous current collector and Si nanoparticles sealed in as an active material. Graphene deposition and pore formation in metal current collector is achieved in a unique single step synthesis. All the active components like current collector, reacting material, and conducting material are manipulated in a way to produce synergistic architecture in a chemical vapor deposition process. Highly pure graphene deposited in this process enables efficient electron transfer from allover of the surface of silicon nanoparticles and prevents continuous solid electrolyte interphase layer formation. This binder free anode assembly shows extremely stable lithium storage performance for over 1000 cycles with 88% of initial capacity retention and 100% Coulombic efficiency. Abstract : A stable anode for Li‐ion batteries based on 3D skeletal current collectors with micron size pore structure and Silicon–graphene active material is reported. When the pores of graphene coated stainless steel current collector are used as microfilling chambers for Silicon nanoparticles that are closed by another blanket layer of graphene, remarkable cyclability and enhanced specific capacity are observed for the anode.